2005
DOI: 10.1016/j.ejheart.2004.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and cardiogenic shock in acute myocardial infarction

Abstract: Aims: Cardiogenic shock is the leading cause of in-hospital mortality after acute myocardial infarction (MI).This study investigates the importance of age and preexisting diabetes mellitus on the incidence and prognosis of cardiogenic shock in a large group of consecutive patients with MI. Methods and results: Baseline characteristics and in-hospital complications to the infarction were prospectively recorded in 6676 patients with MI.Ten-year mortality was collected. Diabetes was present in 10.8% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
9
15
0
Order By: Relevance
“…These results are in agreement with that reported by Lindholm [5] who reported that, the mean age of cases with CS was 74 compared to 69 in cases with acute MI only.…”
Section: The Global Utilization Of Streptokinase and Tissue Plasminogensupporting
confidence: 83%
See 4 more Smart Citations
“…These results are in agreement with that reported by Lindholm [5] who reported that, the mean age of cases with CS was 74 compared to 69 in cases with acute MI only.…”
Section: The Global Utilization Of Streptokinase and Tissue Plasminogensupporting
confidence: 83%
“…These findings agree with the results of Lindholm et al [5] who reported that males represent 67% of all cases with acute MI and represent 68% of cases with CS compared to 60% of cases without CS. This difference was statistically significant.…”
Section: The Global Utilization Of Streptokinase and Tissue Plasminogensupporting
confidence: 83%
See 3 more Smart Citations